2015
DOI: 10.1007/s11676-015-0137-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wollastonite nanofibers on fluid flow in medium-density fiberboard

Abstract: We studied the effect of wollastonite nanofibers on fluid flow in medium-density fiberboard (MDF). Nanowollastonite (NW) was applied in MDF at 10 %, based on the dry weight of wood fibers. We also tested chicken feathers as an additive to the matrix at 5 and 10 % by weight. The weight of feathers was reduced from the wood fibers to keep the density of the panels constant (0.66 g cm -3 ). Wollastonite nanofibers acted as filler in the matrix and significantly decreased gas and liquid permeability. Higher therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Wollastonite-treated panels showed a significant decrease in water absorption for all the three treatments. It was previously reported that wollastonite-treated composite panels had lower gas and liquid permeability [20,26]. In this way, the reinforcement of UF resin by wollastonite caused higher integration of fiber in the composite-matrix, preventing water to easily pass through.…”
Section: Physical Propertiesmentioning
confidence: 93%
See 4 more Smart Citations
“…Wollastonite-treated panels showed a significant decrease in water absorption for all the three treatments. It was previously reported that wollastonite-treated composite panels had lower gas and liquid permeability [20,26]. In this way, the reinforcement of UF resin by wollastonite caused higher integration of fiber in the composite-matrix, preventing water to easily pass through.…”
Section: Physical Propertiesmentioning
confidence: 93%
“…The heat-transferring properties of metals and improving effects of different materials at micro-and nano-scales [12][13][14][15][16][17] were also found to decrease hot press time and to improve the physicomechanical properties in wood composites [6,18]. Under this frame, wollastonite (as a silicate mineral, CaSiO 3 ) was found to improve the biological and physicomechanical properties of both solid wood and wood based panels, as well as to improve the fire retardancy and to increase thermal conductivity coefficient in medium-density fiberboards (MDF) [19][20][21][22][23][24][25][26], therefore, the first aim of the present study was to find out possible effects that wollastonite may have on physical and mechanical properties of two engineering wood composites, namely medium-density fiberboards and particleboards. Based on potential positive results of the addition of wollastonite on properties of composite panels in the present study, future studies on decreasing urea-formaldehyde (UF) resin content, or even using an eco-friendly resin within a green framework, would be predictable and should be carried out, similar to what was previously achieved by the application of tannin in wood-composite panels [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations